Investigating the Effect of Olfactory Stimulation in Preterm Infants: A Review Study - Hashem Lashgari Kalat; Mohammad Hasan Mohammadi; Shahabaddin Sorouri; Hossein Ali Kharazmi; Zahra Ramazanian Bafghi; Masumeh Ghazanfarpour; Najmeh Soltani Nejad (Journal of Pediatrics Review)
Background: Besides respiratory problems, the lack of or inefficient oral feeding performance is a major problem facing premature newborns. Researchers and clinicians need to be aware of procedures and positive olfactory stimuli mediating major problems and more adaptable premature infants to the neonatal intensive care unit and hospital environments. Accordingly, it is essential to undertake a comprehensive review of the effect of olfactory stimulation in preterm infants. Objectives: This study aims to assesses the effect of aromatherapy on apnea, the transition from tube feeding (gavage) to oral feeding, pain, growth and duration of hospital stay. Methods: The major English databases, such as PubMed, Embase, Scopus, Cochrane Library and ISI Web of Science, were systematically reviewed without any time restrictions up to April 12, 2022. Two researchers assessed articles, and any discrepancies were resolved by a third author. The data were extracted through a pre-prepared. The 5-item Jadad scale was used to assess the quality of the articles found in the search. Results: A total of 13 studies were included in the current review. There are controversial results about the aromatherapy effect of pleasant odor vanillin on apnea attacks in preterm infants. Rosa damascenes odor had a therapeutic effect on apnea attacks, but not breast milk odor. The breast milk and the vanillin odor were effective in preterm infants’ venipuncture. Meanwhile, hospital discharge time and transition time from tube feeding to oral feeding were shorter; however, the results were insignificant. Conclusions: Olfactory stimulation by some pleasant odors is a safe, non-invasive and family-friendly intervention and can help improve apnea attacks and painful procedures in preterm infants. There was no clear effect of exposure to pleasant odor on hospital discharge and transition time from tube feeding to oral feeding.